Studi Etnobotani, Edukasi Dan Pemanfaatan Bunga Telang (Clitoria Ternatea) Sebagai Obat Tradisional Tetes Mata Di Pondok Pesantren Salafi Ar-Raaid Cabang, Panyileukan Kota Bandung Jawa Barat - Savira Puji Lestari; Tri Cahyanto (Politeknik Kampar, 2023)
The Telang plant (Clitoria ternatea) is a traditional climbing plant that belongs to the fabaceae or legume group. Its way of life is like climbing on house fences, it can even spread on other plants. The benefits that can be taken from the roots to the top of the telang plant have been widely used by Indonesian people, one of which is the flower part as a traditional eye drop. This butterfly pea flower water extract has antibacterial and anti-inflammatory properties. Of course, these traditional eye drops are natural so they can mitigate the effects of synthetic eye drops. Butterfly pea flowers have a variety of colors, including white, blue and purple. However, the color of butterfly pea flowers that is often seen around the yard is dark blue. This is because telang flowers contain anthocyanin which is a group of water-soluble pigments. Apart from traditional medicine, butterfly pea flowers can also be used for food as a natural dye. This research took place in the Cipadung Wetan sub-district, Panyileukan District, East Bandung Regency. The method used is a qualitative method because the information conveyed is in the form of education and direct use to several female students at the Arraid Salafi Islamic Boarding School regarding traditional eye drops which are quite easy to administer. One of the ethnobotanical studies delivered was about a very easy way to cultivate butterfly pea plants, namely by planting the seeds.